2008
DOI: 10.1016/j.bbcan.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating and cell-targeting peptides in drug delivery

Abstract: During the last decade, the potential of peptides for drug delivery into cells has been highlighted by the discovery of several cell-penetrating peptides (CPPs). CPPs are very efficient in delivering various molecules into cells. However, except in some specific cases, their lack of cell specificity remains the major drawback for their clinical development. At the same time, various peptides with specific binding activity for a given cell line (cell-targeting peptides) have also been reported in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
272
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(284 citation statements)
references
References 160 publications
3
272
0
6
Order By: Relevance
“…CPP-based cargo has various advantages over the viral gene delivery methods in mammalian cells as CPPs are free of infectious material and can be stored freeze dried without causing any change in their properties. Additionally, CPPs alone and their cargoes have low levels of cytotoxicity at the concentration at which CPPs are used for the delivery of macromolecules (2). We have also observed that internalization of cargoes of CPPs, such as Tat and its dimmer, is nondeleterious to plant cells (3).…”
Section: Introductionmentioning
confidence: 62%
“…CPP-based cargo has various advantages over the viral gene delivery methods in mammalian cells as CPPs are free of infectious material and can be stored freeze dried without causing any change in their properties. Additionally, CPPs alone and their cargoes have low levels of cytotoxicity at the concentration at which CPPs are used for the delivery of macromolecules (2). We have also observed that internalization of cargoes of CPPs, such as Tat and its dimmer, is nondeleterious to plant cells (3).…”
Section: Introductionmentioning
confidence: 62%
“…Until one of the methods of cell membrane penetration is not considered to be the most dominant and reliable, it can be assumed that each of the above-described transport pathways may be involved in the penetration of CPPs depending on their concentration, hydrophobicity, or other physicochemical parameters. The method of CPP penetration into cells can also be affected by the charge type, the class of CPP, the cell line used in the experiment, and incubation conditions [55].…”
Section: Energy-dependent Endocytosis-mediated Cellular Uptakementioning
confidence: 99%
“…TAT peptide conjugation has been shown to enhance the cellular uptake of doxorubicin-loaded liposomes, as well as improving transfer across the blood brain barrier in in vitro models 8 . TAT-based modification through the formation of direct links to the liposome surface, however, can lead to endocytosis and a lack of cell-specificity, which in turn accelerates elimination through the mononuclear phagocyte system 9 .…”
mentioning
confidence: 99%